More than 50% of Clostridium difficile Isolates from Pet Dogs in Flagstaff, USA, Carry Toxigenic Genotypes - Stone, Nathan E.; Sidak-Loftis, Lindsay C.; Sahl, Jason W.; Vazquez, Adam J.; Wiggins, Kristin B.; Gillece, John D.; Hicks, Nathan D.; Schupp, James M.; Busch, Joseph D.; Keim, Paul; Wagner, David M. (PLOS ONE, 2016)
Nosocomial acquisition of Clostridium difficile is well documented, yet recent studies have highlighted the importance of community acquired infections and identified community associated reservoirs for this pathogen. Multiple studies have implicated companion pets and farm animals as possible sources of community acquired C. difficile infections in humans. To explore the potential role of pet dogs in human C. difficile infections we systematically collected canine fecal samples (n = 197) in Flagstaff, AZ. Additionally, nineteen fecal samples were collected at a local veterinary clinic from diarrheic dogs. We used these combined samples to investigate important questions regarding C. difficile colonization in pet canines: 1) What is the prevalence and diversity of C. difficile in this companion pet population, and 2) Do C. difficile isolates collected from canines genetically overlap with isolates that cause disease in humans? We used a two-step sequence typing approach, including multilocus sequence typing to determine the overall genetic diversity of C. difficile present in Flagstaff canines, and whole-genome sequencing to assess the fine-scale diversity patterns within identical multilocus sequence types from isolates obtained within and among multiple canine hosts. We detected C. difficile in 17% of the canine fecal samples with 10% containing toxigenic strains that are known to cause human disease. Sequencing analyses revealed similar genotypes in dogs and humans. These findings suggest that companion pets are a potential source of community acquired C. difficile infections in humans.